Progressive Lung Injury, Inflammation, and Fibrosis in Rats Following Inhalation of Sulfur Mustard. (1st October 2020) - Malaviya, Rama; Abramova, Elena V; Rancourt, Raymond C; Sunil, Vasanthi R; Napierala, Marta; Weinstock, Daniel; Croutch, Claire R; Roseman, Julie; Tuttle, Rick; Peters, Eric; Casillas, Robert P; Laskin, Jeffrey D; et al.
Abstract: Sulfur mustard (SM) inhalation causes debilitating pulmonary injury in humans which progresses to fibrosis. Herein, we developed a rat model of SM toxicity which parallels pathological changes in the respiratory tract observed in humans. SM vapor inhalation caused dose (0.2–0.6 mg/kg)-related damage to the respiratory tract within 3 days of exposure. At 0.4–0.6 mg/kg, ulceration of the proximal bronchioles, edema and inflammation were observed, along with a proteinaceous exudate containing inflammatory cells in alveolar regions. Time course studies revealed that the pathologic response was biphasic. Thus, changes observed at 3 days post-SM were reduced at 7–16 days; this was followed by more robust aberrations at 28 days, including epithelial necrosis and hyperplasia in the distal bronchioles, thickened alveolar walls, enlarged vacuolated macrophages, and interstitial fibrosis. Histopathologic changes were correlated with biphasic increases in bronchoalveolar lavage (BAL) cell and protein content and proliferating cell nuclear antigen expression. Proinflammatory proteins receptor for advanced glycation end product (RAGE), high-mobility group box protein (HMGB)-1, and matrix metalloproteinase (MMP)-9 also increased in a biphasic manner following SM inhalation, along with surfactant protein-D (SP-D). Tumor necrosis factor (TNF)-α and inducible nitric oxide synthase (iNOS), inflammatory proteins implicated in mustard lung toxicity, and the proinflammatory/profibrotic protein, galectin (Gal)-3, were upregulated in alveolar macrophages and in bronchiolar regions at 3 and 28 days post-SM. Inflammatory changes in the lung were associated with oxidative stress, as reflected by increased expression of heme oxygenase (HO)-1. These data demonstrate a similar pathologic response to inhaled SM in rats and humans suggesting that this rodent model can be used for mechanistic studies and for the identification of efficacious therapeutics for mitigating toxicity.